ANALISIS BIBLIOMETRIC DARI PROGRAM HIBAH (BIBLIOMETRIC OF GRANTS PROGRAM) - Iqbal M. Iqbal Firmansyah; Rita Myrna; Ida Widianingsih (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2021)
This article is a bibliometric analysis of articles published in Scopus indexed journals that discuss grant programs using Vosviewer. The purpose of bibliometric analysis is aimed at knowing the development of studies related to the grant program. Specifically, this study looks at the development of citations, publication trends, author collaboration, trend terms titles, trend terms author keywords, trend terms abstracts, and state statistics on grant program articles in 2015-2020. Data were collected from the Scopus database using the keyword